The Influence of Brand Image, Price, Product Quality, and Distribution on Purchase Decisions for Fiesta Chicken Nugget Products (Smart Superstore Medan City) - Andriasan Sudarso; Lili Suryati; Lenny Menara Sari Saragih; Fajrillah Fajrillah; Shamir Hasyim Syarif; Klara Ratna Putri Nazara (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the effect of brand image, price, product quality, and distribution on decisions in purchasing products from Fiesta Chicken Nugget (Smarco Superstore, Medan City). The results of the multiple linear regression test Y= 1.409 + 0.102X1 - (-0.045) X2 + 0.711X3 + 0.127X4+e. The results showed that partially Brand Image, Price, Product Quality, and Distribution, on the Purchase Decision of Fiesta Chicken nuggets. And the results of the study simultaneously showed that Brand Image, Price, Product Quality, and Distribution, had a significant and significant effect on Purchase Decisions. The coefficient of determination obtained for the partial effect of Brand Image, Price, Product Quality, and Distribution, on Purchase Decisions is obtained by 70%, while the remaining 30% is influenced by other factors not examined in this study.